IMPLEMENTASI PROGRAM SEKOLAH ANTI BULLYING DI SMP NEGERI 2 TEMANGGUNG - Neria Sukowati; Ngurah Ayu Nyoman Murniati; I Made Sudana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sukowati, Neria. 2024. Implementation of the Anti-Bullying School Program at SMP Negeri 2 Temanggung. Thesis. Education Management Study Program. Postgraduate Program at Universitas PGRI Semarang. Supervisors 1) Dr. Ngurah Ayu Nyoman Murniati, M.Pd., 2) Dr. I Made Sudana, M.Pd. This research discusses the implementation of the anti-bullying school program at SMP Negeri 2 Temanggung. The study aims to explore the effectiveness of the program in creating a safe and comfortable learning environment for students. Using a qualitative approach, data was collected through interviews, observations, and documentation to analyze the planning, implementation, and evaluation of the program. The results indicate that the anti-bullying school program has been effectively implemented, evidenced by a decrease in the number of bullying cases in the school. The program involves all school elements, including students, teachers, and parents, and applies positive discipline focused on the prevention and handling of bullying behavior. Although challenges remain in addressing the still-dominant verbal bullying, this collaborative effort has increased awareness and student participation in creating a safer environment. This research is expected to contribute to the development of educational policies and school management practices in the prevention of bullying. Additionally, the findings may serve as a reference for further research related to the implementation of anti-bullying programs and character education in school environments.